Improving Employee Productivity Through Supervision: A Case Department of Manpower, Indramayu - Qodariah Qodariah; Syaiful Anwar (UNIVED Press, 2024)
In this study, the Manpower Depatment in Indramayu needs to evaluate factors that can increase the productivity of its employees, especially in providing services to the community with the aim of being able to provide excellent service to the community and participate in reducing unemployment in Indramayu, dynamically and stimulate the community to take advantage of every job opportunity, able to create jobs so as to obtain a decent income so that in the end a reliable, dynamic and independent workforce can be realized as soon as possible. The productivity of the employees of the Department of Labor in Indramayu, needs to be further reviewed in this study. This study uses a path analysis model with smartPLS software. The population of this study are employees of the Department of Manpower in Indramayu Regency. The research sample is all civil servants totaling 56 people. The research results prove that discipline and competence can affect employee supervision. Supervision is also proven to be able to increase employee productivity. Indirect influence from discipline and competence also prove capable of influencing employee productivity through supervision Department of Manpower in Indramayu. Variables that contribute the greatest supervision on work productivity.